Atendimento nos polos EAD de uma universidade pública: avaliação dos alunos - Souza, Andrea Gonçalves Mariano (2020)
This research aims to analyze the quality of care provided by the Poles of a state public institution, in the evaluation of the students themselves, establishing, as objectives, the understanding of the process of creating a state public institution that offers, exclusively, education superior in the distance modality from the knowledge of the relevant legislation, specific to the regulation of Distance Education, at the state and federal level; the concept of quality considered in the provision of service to the student; verification of the institution's expansion; finally, forward the students' suggestions to improve the services provided by the Higher Education Institution (HEI. This is a qualitative and quantitative research, with data collection carried out through a questionnaire, a survey implemented based on the content analysis based on Bardin (2016). 1,573 responses were obtained from a group of 8,177 students who received the questionnaire. From the set obtained, it was possible to infer that students are satisfied with the Pole and with the channels available for contact. , but in the qualitative data it is possible to identify a distinction - pointed out by the students - between the Pole and the institution (headquarters), considered as distinct organizations.The research showed satisfaction on the part of the students in relation to the Poles, although they have presented some critical notes in the the institution (headquarters). It is concluded that there is a need to improve the institution's internal practices, providing greater transparency in communication with students, agility in correcting tests, availability of face-to-face tutors at the Hubs, training of professionals who provide services at the Hubs and better communication between the institution's headquarters and the Distance Education Hub.